(untitled) (Journal of actual problems of jurisprudence, 2023)
The article discusses with the authors the role of environmental education in improving environmental culture and ensuring environmental safety. Environmental safety is an integral part of overall safety. Environmental safety in turn, environmental law extends to structural levels of order and is the organizational, legal and informational core of Environmental Law Order. Environmental law is understood as the sphere of mutual influence or action of society and nature, based on legal norms that ensure the environmental safety of people and citizens. The category of Environmental Law is very little studied at this time, that is, it is rarely used in the field of modern law, including in the field of Environmental Law. In addition, it has important theoretical and practical significance on the way to the formation and improvement of environmental legislation. The need for the development and formation of the concept of Environmental Law and order is obvious. Environmental order and environmental safety are interrelated, and the first of them is a qualitative characteristic of the second. Our country pays great attention to environmental issues, including improving the ecological culture of the population on Environmental Protection. One of the mechanisms for achieving environmental safety and ensuring sustainable development is to achieve it through environmental education and increasing the environmental culture as a whole. Keywords ecology, environmental law and order, environmental safety, environmental education, environmental culture, environmental information.